(untitled) (Medical Forum Monthly, 2022)
Objective: To find out the prevalence of vitamin B12 deficiency among the patients with type-II diabetes mellitus using metformin. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the Abbasi Institute of Medical Sciences Muzaffarabad. Study was completed in six months duration from July 2021 to December 2021 for a period of six months. Materials and Methods: All previously diagnosed cases with type-II diabetes mellitus using metformin for more than six months duration was included in this study. Blood level of vitamin B12 was measured in all cases. SPSS-17 software was used for data analysis. P-value <0.05 was taken statistically significant. Results: Total 200 cases were studied including 127(63.5%) male and 73(36.5%) female cases. 23% diabetic patients using metformin were having vit-B12 deficiency with the blood level <150 pg/ml. age range of the patients was 30-75 years with mean age of 45.7 ± 5.8 years. Smokers were having more incidence of vit-B12 deficiency than non-smokers. Use of multivitamins prevent B-12 deficiency. Conclusion: Use of metformin in diabetes mellitus is strongly associated with B-12 deficiency, so endocrinologist and physician should evaluate diabetic patients for B-12 deficiency and treat it properly.